Pengaruh E-book DAGUSIBU Terhadap Pengetahuan dan Perilaku Swamedikasi Obat Pada Anggota Pemberdayaan Kesejahteraan Keluarga - Putu Wulan Octa Viana; Ni Putu Aryati Suryaningsih; Gde Paguna Reganata; I Gusti Ayu Rai Widowati (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
Inappropriate use of medicines, whether prescribed by physicians or used for self-medication, poses a risk of medication errors and threatens patient safety. One of the contributing factors is the low level of public literacy in proper drug management based on the DAGUSIBU principles (Obtain, Use, Store, and Dispose). This study aimed to determine the effect of the DAGUSIBU e-book on improving knowledge and self-medication behavior among members of the PKK in Banjar Sigaran, Desa Sedang. This research employed a pre-experimental method with a one-group pretest–posttest design involving 50 respondents selected using a consecutive sampling technique. The research instruments consisted of knowledge and behavior questionnaires based on the DAGUSIBU concept and the Theory of Planned Behavior (TPB). The majority of respondents were aged 36–45 years (40%), had a secondary level of education (58%), were housewives, and had an income below the regional minimum wage (44%). The Wilcoxon test was applied because the data were ordinal and not normally distributed. The results indicated an improvement in the knowledge category from poor (62%) to moderate (62%) and a change in behavior from negative (52%) to positive (60%) after the intervention. A significant effect was found between the use of the e-book and the levels of knowledge and self-medication behavior (p-value < 0.001). In conclusion, the DAGUSIBU e-book as a digital educational medium is proven to have a significant effect in supporting the improvement of drug management literacy at the household level.